Some questions of developing an adaptive educational environment in professional (vocational) education institutions - Davydova, Y. (Problems of Engineer-Pedagogical Education, 2019)
The article is devoted to the problem of developing an adaptive educational environment in professional (vocational) education institutions, which carry out vocational training of skilled workers in the construction sector. The article specifies the peculiarities of training skilled construction workers. It also partially reveals the essence of adaptive educational environment in the system of professional (vocational) education. The outcome of the research highlights that the training of skilled construction workers in professional (vocational) education institutions requires significant changes: updating the content of vocational training; informatization of the teaching-learning process by the means of creating the e-learning space in each institution; reorienting the teaching-learning process from the substantive towards competence-based approach; introducing the newest pedagogical and production technologies; improving professional level of the teaching staff by increasing their motivation for continuing professional development. The survey results show the level of readiness to develop an adaptive educational environment for participants of the teaching-learning process in professional (vocational) education institutions among the construction professions in the Kharkiv region. The survey of pedagogical workers and students reveals a common view on the problems among all participants of the teaching-learning process; the real situation of the vocational training of skilled construction workers in professional (vocational) education institutions of the Kharkiv region; the strengths and weaknesses of the organization of the teaching-learning process. The necessity of building a new educational environment for skilled construction workers training by improving its quality not only provides the affordable quality education for all strata of the society but also gives the opportunity for our education to become competitive both on the regional and European labor market.